Implementasi Konsep “Harmony in Equality” pada Desain Interior Sekolah Inklusi Galuh Handayani Surabaya - Florentina Tamariska Wijaya; Ronald Hasudungan Irianto Sitinjak; Linggajaya Suryanata (Intra, 2018)
Education of children with special needs has been included in the Law of the Republic of Indonesia Number 20 Year 2003 on the National Education System, The government of Surabaya is now advising each school to have inclusion classes to accommodate special needs student so that they can pursue equal education opportunities and can develop by maximizing their potential. In order to achieve that objective, Galuh Handayani Inclusive School requires spesific interior design so that the school can provide better teaching. This design uses the method of design thinking Veronique Hillen, consisting of three major stages consist of inspiration, ideation, and implementation. “Harmony in Equality” interior design is able to assist the process of development of special needs children such as by create conducive condition in terms of interior and surrounding environment for ABK to move independently. In accordance with the “Harmony in equality” concept, use of wayfinding with color coding so that the interior of the school is more accessible for special needs children. Selected material and finishing, circulation, interior elements and interior systems that can meet the needs of the crew is universally important to apply. Interior Design of Galuh Handayani Inclusive School in Surabaya help parents or disability learners in education and therapy aspects, able to improve public health and creating an independent and trained ABK so the Inclusion School Galuh Handayani can be a pioneer of inclusive schools in Indonesia.